EFEKTIVITAS PENGGUNAAN TERAVERSA UNIVERSITAS JENDERAL SOEDIRMAN PURWOKERTO DI DALAM INOVASI KEBIJAKAN PUBLIK - Yuristrianti, Nurrekta; Yusuf, Imam Maulana; Rokhman, Ali (Program Studi Ilmu Pemerintahan FISIP Universitas Galuh, 2025)
This research examines the effectiveness of using Teraversa Unsoed Purwokerto in public policy innovation. Teraversa is a platform that brings together historians, government, and the community to formulate policies that are responsive to public needs. The study employs a qualitative descriptive method, with data collected through interviews, observations, and documentation of decision-making processes and policy implementation. Data analysis uses thematic analysis to identify key themes.The results show that Teraversa plays an important role in improving the quality of public services by developing innovative policies. Teraversa enhances community participation, facilitates cross-sectoral communication, and promotes good governance. In addition, this initiative reduces bureaucracy and increases service efficiency. The challenges encountered include policy socialization and the development of human resource capacity, including initial resistance from local governments and communities who have not yet understood its benefits. Intensive training is required to improve the competence of the Teraversa team in designing and implementing complex policies. It is concluded that Teraversa has great potential in supporting public policy innovation, with the need for better implementation strategies and strengthened partnerships with various stakeholders, as well as periodic evaluations to enhance policy effectiveness.